Prevalence of SARS-CoV-2 infection and associated risk factors: A testing program and nested case-control study conducted at Sapienza University of Rome between March and June 2021 - Baccolini, Valentina; Siena, Leonardo Maria; Renzi, Erika; Migliara, Giuseppe; Colaprico, Corrado; Romano, Alessandra; Massimi, Azzurra; Marzuillo, Carolina; De Vito, Corrado; Casini, Leandro; Antonelli, Guido; Turriziani, Ombretta; et al. (Frontiers in Public Health, 2022)
Background. To safely resume in-person activities during the COVID-19 pandemic, Sapienza University of Rome implemented rigorous infection prevention and control measures, a successful communication campaign and a free SARS-CoV-2 testing program. In this study, we describe the University’s experience in carrying out such a program in the context of the COVID-19 response and identify risk factors for infection. Methods. Having identified resources, space, supplies and staff, from March to June 2021 Sapienza offered to all its enrollees a molecular test service (8.30 AM to 4 PM, Monday to Thursday). A test-negative case-control study was conducted within the program. Participants underwent structured interviews that investigated activity-related exposures in the two weeks before testing. Multivariable conditional logistic regression analyses were performed. Adjusted odds ratios (aORs) and 95% confidence intervals (95% CIs) were calculated. Results. A total of 8959 tests were administered, of which 56 were positive. The detection trend followed regional tendencies. Among 40 cases and 80 controls, multivariable analysis showed that a known exposure to a COVID-19 case increased the likelihood of infection (aOR: 8.39, 95% CI: 2.38-29.54), while having a job decreased it (aOR: 0.23, 95% CI: 0.06-0.88). Of factors that almost reached statistical significance, participation in activities in the university tended to reduce the risk (aOR: 0.32, 95% CI: 0.09-1.06), while attendance at private gatherings showed an increasing risk trend (aOR: 3.48, 95% CI: 0.95-12.79). Age, gender, activities in the community, visiting bars or restaurants, and use of public transportation were not relevant risk factors. When those students regularly attending the university campus were excluded from the analysis, the results were comparable, except that attending activities in the community came close to having a statistically significant effect (aOR: 8.13, 95% CI: 0.91-72.84). Conclusions. The testing program helped create a safe university environment. Furthermore, promoting preventive behavior and implementing rigorous measures in public places, as was the case in the university setting, contributed to limit the virus transmission.